Structure design and mechanical performance analysis of three kinds of bioresorbable poly-lactic acid (PLA) stents. Issue 1 (2nd January 2023) - Wang, Yangyang; Wu, Hongmei; Fan, Shiyi; Wu, Jingzhi; Yang, Sisi
Abstract: Vascular stent implantation has become an important choice for the treatment of severe cardiovascular and cerebrovascular blockage. Rational design is vital to ensure the mechanical properties of the vascular stents, which are important both to the implantation and service as for clinical treatment of coronary heart disease. Therefore we proposed a wholly new non-uniform honeycomb stent E and compared with an inverted honeycomb-like shaped stent F and a honeycomb-like shaped stent G. To evaluate their properties, a finite element method (FEM) was used to simulate the implantation process (crimp, crimp recoil, expand, and expand recoil) of these three different kinds of stents. Results showed that the stent E exhibits better mechanical behaviour than the other two stents F and G as far as radial strength and axial shortening performances and that the distribution of equivalent stress among the stent E is more uniform than that among the other two stents F and G. After that, a three-point bending method was used to study the bending flexibility of these three vascular stents. Stent E shows high bending stiffness compared with stents F and G due to the existence of additional support bridges in its structure. This study can be helpful to the rational design of optimizable PLA stents for its practical clinical performance and therefore possibly improve the prognosis of patients.